2018
DOI: 10.1002/ejic.201801118
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Relation between Structure and Aggregation Induced Emission (AIE) Properties of Iridium(III) Complexes through Modification of Non‐Chromophoric Ancillary Ligands

Abstract: Unconventionally modified dibenzoylmethane (dbm) ligands have been synthesized and successfully utilized as ancillary ligands for neutral iridium(III) complexes of the formula [Ir(dFppy)2(LX)], where dFppyH is 2‐(2,4‐difluorophenyl)pyridine and LX is tribenzoylmethane (tbm) or 1‐phenyl‐3‐(4‐(pyridin‐2‐yl)phenyl)propane‐1,3‐dione (pydbm). The modification of the ligands aims to prevent or enhance possible intermolecular interactions between the dFppy and/or the LX moiety in comparison with the previously report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Compounds with a tendency to aggregation-induced emission (AIE) are sought after, mainly due to the possibility of their wide application in organic electronics, i.e., OLEDs or cellular imaging [2]. Sometimes an insignificant change of properties allows AIE-gens to be obtained [47][48][49][50]. Therefore, as part of the work, we present research on the properties of compounds in the aggregated state.…”
Section: Photoluminescence In Aggregated Statementioning
confidence: 99%
“…Compounds with a tendency to aggregation-induced emission (AIE) are sought after, mainly due to the possibility of their wide application in organic electronics, i.e., OLEDs or cellular imaging [2]. Sometimes an insignificant change of properties allows AIE-gens to be obtained [47][48][49][50]. Therefore, as part of the work, we present research on the properties of compounds in the aggregated state.…”
Section: Photoluminescence In Aggregated Statementioning
confidence: 99%
“…[23] Many pure organic mechanochromic materials with AIE-activem olecules were thus reported, [24][25][26][27][28][29][30][31] along with organoboron complexes. [32,33] Regarding metal-based compounds that combine AIE and mechanochromic properties, few studies have been reported, with examplesb ased on iridium(III), [34][35][36][37][38][39] cadmium(II), [40] zinc(II), [41,42] and gold(I) [43] complexes.…”
Section: Introductionmentioning
confidence: 99%
“…We synthesized the ligands according to the conventional procedure ( S2‐1 ). The precursor phenyl bromide derivatives can be prepared according to the literature procedure [37, 38] . Then, a Buchwald‐Hartwig coupling reaction of dimethylacridine (DMAC) with the phenyl bromide derivatives were subsequently conducted; L‐1 and L‐2 achieved yields of 84 % and 78 %, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thep recursor phenyl bromide derivatives can be prepared according to the literature procedure. [37,38] Then, aB uchwald-Hartwig coupling reaction of dimethylacridine (DMAC) with the phenyl bromide derivatives were subsequently conducted; L-1 and L-2 achieved yields of 84 % and 78 %, respectively.T he ligands were purified by train sublimation before device fabrication.…”
Section: Resultsmentioning
confidence: 99%